Compassion in dementia caregiving: Psychometric properties of the Caregiving Compassion Scale in Spanish caregivers. (21st November 2021) - Gallego‐Alberto, Laura; Romero‐Moreno, Rosa; Márquez‐González, María; Schulz, Richard; Cabrera, Isabel; Olazarán‐Rodríguez, Javier; Losada, Andrés
Abstract: Compassion has been suggested as a relevant variable for understanding dementia caregivers' psychological distress. The objectives were to analyse the psychometric properties of the Caregiving Compassion Scale (CCS) and to explore the association between caregivers' compassion and their emotional health. Two hundred and thirty‐six dementia caregivers were evaluated for compassion, depressive symptoms, guilt, ambivalence, care‐recipient's functional and cognitive status, frequency of behavioural problems and desire to institutionalise the care‐recipient. Exploratory factor analyses, correlations and regression analyses were done. Two factors were obtained. The factor labelled "Distress from witnessing the care recipient suffering" was associated with higher stress linked to witness depressive problems in the care‐recipient and with caregivers' ambivalence and guilt levels. The factor labelled "Motivation/disposition for helping" was associated with less desire for institutionalisation, and it showed a negative association with ambivalence and guilt feelings. The CCS seems to be a valid and reliable scale for assessing compassion in dementia caregivers.